2023
DOI: 10.1007/s40839-023-00195-z
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Moral Foundations Questionnaire within a Muslim society: a study among young adults in Pakistan

Abstract: This paper examines the psychometric properties of the 30-item Moral Foundations Questionnaire among a sample of 370 young adults between the ages of 18 and 26 years who were born in Punjab and who had lived there since their birth. Initial analyses did not support the internal consistency reliability of the five scales of moral predispositions proposed by this measure. Exploratory factor analysis and confirmatory factor analysis identified two factors that distinguished not between areas of moral predispositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Notably, the study's findings also touched upon the impact of family system structures on caregiving stress, revealing no significant relationship between stress levels and whether the family was nuclear or joint. This observation is particularly relevant in the context of Pakistani society (35). While the nuclear family trend presents both challenges and advantages, it underscores the importance of robust social support systems for caregivers, an area that merits further exploration (36).…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the study's findings also touched upon the impact of family system structures on caregiving stress, revealing no significant relationship between stress levels and whether the family was nuclear or joint. This observation is particularly relevant in the context of Pakistani society (35). While the nuclear family trend presents both challenges and advantages, it underscores the importance of robust social support systems for caregivers, an area that merits further exploration (36).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, using the longer version of MFQ (30 items), a set of studies found support for the five-factor model over alternative models (as was the case of the original study (Graham et al, 2011)), although the model fit of the five-factor model was not optimal (see also Nilsson & Erlandsson, 2015;Yilmaz et al, 2016). Other studies, on the other hand, failed to identify the proposed five-factor structure (Akhtar, Francis, Village et al, 2023;Iurino & Saucier, 2020). We'll come back to this issue later.…”
Section: Discussionmentioning
confidence: 98%
“…Another study in the United Kingdom also failed to replicate the five-factor model originally proposed by Graham et al (2011) and suggested that “compassion” and “traditionalism” may account for the structure of the MFQ-1 in the United Kingdom (Harper & Rhodes, 2021). A recent factor-analytic study with young Muslim adults in Pakistan also found that the MFQ-1 has psychometric limitations and cannot be reliably used to measure the original five moral foundations in Punjab (Akhtar et al, 2023).…”
Section: Mft and The Mfqmentioning
confidence: 99%